IDENTIFIKASI STRUKTUR GEOLOGI DENGAN GEOLISTRIK METODE SCHLUMBERGER STUDI KASUS SEBAGIAN SISI UTARA KAMPUS UNIVERSITAS DIPONEGORO TEMBALANG - Prasetyo, Sigit (Geological Engineering E-Journal, 2013)
Geoelectric (resistivity) is a geophysical method used to determine the condition or the subsurface geological structures based on the variation of the resistivity rock. What the research lies in the northern part UNDIP Tembalang campus, located on Kaligetas Formation (Qpkg) lithological units composed of volcanic breccia, lava flows, tuffs, tuffaceous sandstone and mudstone. At the study site found the scarp and alignment springs. The condition is likely due to the influence of geological structures formed. The purpose of this study was to determine the subsurface lithology types andÂ  kinds of geological structures based on the measurement results Schlumberger geoelectric method.The method used in this study is geoelectric schlumberger method. Geoelectric measurements carried out by 16 points spread among the sites. Geoelectric data processing to determine the actual value of resistivity and thickness of each layer using software IPI2win.Based on the results of data processing geoelectric resistivity values obtained in the study area in the form of rock mudstone (â¤ 15 Î©m), sandy mudstone (16-45 Î©m), sandstones (46-100 Î©m), and volcanic breccia (> 100 Î©m). The results of the resistivity values and correlated geoelectric section is to analyze the structural phenomenon which occurs in the study area. In correlation A - A (UNDIP 3, UNDIP 13, and UNDIP 15) mudstone layer located at a depth of 55 meters in cross UNDIP 3, has increased to lie at a depth of 9 meters in cross section UNDIP UNDIP 13 and 15. In correlation C - C (UNDIP 4, UNDIP 2, and UNDIP 16) mudstone layer located at a depth of 62 meters in cross UNDIP 4, has increased to lie at a depth of 11 meters in cross UNDIP 2 and located at a depth of 2.4 meters in cross UNDIP 16. From the results of which showed increased geoelectric mudstone layer, it can be analyzed that the geological structure in the area of research in the form of faults (fault), the type of reverse faults, the south is part of a down (foot wall), while the northern part is relatively rise blocks ( hanging wall). With the direction of fault trending northwest - southeast